TOURISM DEVELOPMENT AND SOCIO-ECONOMIC CHANGES IN THE COMMUNITY OF MORELLA VILLAGE, LEIHITU DISTRICT, CENTRAL MALUKU REGENCY - Lalihun, Ishaka (Gema Kampus IISIP YAPIS Biak, 2025)
This study aims to explain and analyze the socio-economic changes of the Morella Country Community in Tourism Development. This research method is carried out with a qualitative approach with the State paradigm of Post-Positivism. informants as many as 22 people. Data collection using in-depth interviews, observations and documentation. The data were analyzed using qualitative analysis techniques. The results showed that tourism development in Morella Country focuses on the economy, job creation, and preservation of culture and natural beauty. However, it is necessary to strengthen policies in the use and preservation of tourism objects in Morella Country to achieve this goal. The positive economic and social impact of tourism is seen in the ability of local people to save and improve their living conditions.